Autonomia das declarações de parte como meio de prova - Melo, Duarte Nuno Gomes de Melo e Castro e (2022)
This report follows the Curricular Internship, developed at the Central Civil Court of Lisbon. The theme addressed stems from the concern we felt about the consequences of a tendency to devalue the evidence through statements of part, and a future agglutination of this way of proving to the evidence by witness. Thus, the object of study, here, is proof by statements of part, and our approach will focus on the inclusion of this in the typical cast of evidence, being a defense of the autonomy of this means of proof, considered as an overcoming of the nemo debet principle this testis in propria cause of the legal system. For this reason, it was up to us an analysis of proof, that is, the general features that characterize it in our legal system, an analysis that allows us a better framework of the means of proof in question, as well as the identification of how a fact is demonstrated in the process of forming the judge's conviction. Consequently, it is easier to understand that the weaknesses that the statements of part go through are not reason to degrade the importance that the knowledge of the parties have as a means of proof. It was also necessary to compare, in the sense of the differentiation of that means of proof from the parties' testimonies, due to the bipartisany in the procedural regime for the production of oral evidence by the parties, between the parties' testimony and the statements of the parties. We believe that we have been able to contribute to the inversion, understandable but unwanted, of the tendency to discredit pro pronunciatio statements, through this concatenated and contextualized analysis of this means of proof.